Antibiotic Resistance and Biofilm Infections in the NICUs and Methods to Combat It - Maria Baltogianni; Vasileios Giapros; Chrysoula Kosmeri (MDPI AG, 2023)
Neonatal sepsis is an important cause of neonatal morbidity and mortality. A significant proportion of bacteria causing neonatal sepsis is resistant to multiple antibiotics, not only to the usual empirical first-line regimens, but also to second- and third-line antibiotics in many neonatal intensive care units (NICUs). NICUs have unique antimicrobial stewardship goals. Apart from antimicrobial resistance, NICUs have to deal with another problem, namely biofilm infections, since neonates often have central and peripheral lines, tracheal tubes and other foreign bodies for a prolonged duration. The aim of this review is to describe traditional and novel ways to fight antibiotic-resistant bacteria and biofilm infections in NICUs. The topics discussed will include prevention and control of the spread of infection in NICUs, as well as the wise use of antimicrobial therapy and ways to fight biofilm infections.